Factorial Structure of the EOCL-1 Scale to Assess Executive Functions - Ramos-Galarza, Carlos; Cruz-Cárdenas, Jorge; Bolaños-Pasquel, Mónica; Acosta-Rodas, Pamela (Frontiers in Psychology, 2021)
The process of assessing executive functions through behavioral observation scales is still under theoretical and empirical construction. This article reports on the analysis of the factorial structure of the EOCL-1 scale that assesses executive functions as proposed by the theory developed by Luria, which has not been previously considered in this type of evaluation. In this scale, the executive functions taken into account are error correction, internal behavioral and cognition regulatory language, limbic system conscious regulation, decision making, future consideration of consequences of actions, goal-directed behavior, inhibitory control of automatic responses, creation of new behavioral repertoires, and cognitive-behavioral activity verification. A variety of validity and reliability analyses were carried out, with the following results: (a) an adequate internal consistency level of executive functions between α =.70 and α = .83, (b) significant convergent validity with a scale that assesses frontal deficits between r = -.07 and r = .28, and (c) the scale’s construct validity that proposes a model with an executive central factor CFI = .93, RMSEA = .04 (LO .04 and HI .04), SRMR = .04 and x2(312) = 789.29, p = .001. The findings are discussed based on previous literature reports and in terms of the benefits of using a scale to assess the proposed executive functions.